2001
DOI: 10.1093/hcr/27.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Admirer-celebrity relationships among young adults. Explaining perceptions of celebrity influence on identity

Abstract: This study investigated young adults' judgments regarding the degree to which relationships with celebrity idols influenced their sense of identity and feelings of were recruited from a larger sample (N = 213) of young adults whose responses to a brief survey instrument indicated that they were moderately to strongly attracted to media figures they identified as idols in their lives. The present paper discusses the characteristics of the sample of idols participants reported as well as descriptive data concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 28 publications
7
89
1
5
Order By: Relevance
“…Religious leaders and news commentators were least frequently selected (0.9% and 0.1%, respectively). This breakdown closely mirrored that identified by Boon and Lomore (2001), where 33.9% of respondents chose singers or musicians and 32.3% favoured actors or actresses.…”
Section: Favourite Celebritysupporting
confidence: 78%
See 1 more Smart Citation
“…Religious leaders and news commentators were least frequently selected (0.9% and 0.1%, respectively). This breakdown closely mirrored that identified by Boon and Lomore (2001), where 33.9% of respondents chose singers or musicians and 32.3% favoured actors or actresses.…”
Section: Favourite Celebritysupporting
confidence: 78%
“…A Canadian telephone study of 75 undergraduates found that 58.7% believed their favourite celebrity had influenced their attitudes and beliefs, or had inspired them to pursue a particular activity (Boon & Lomore, 2001). These researchers were not, however, able to conclude whether these influences were largely positive or negative in nature.…”
Section: Introductionmentioning
confidence: 99%
“…As celebrities often represent aspirational reference groups (Escalas, 2004), any para-social relationship is likely to enhance the consumer's desired self (Dwivedi, Johnson, & McDonald, 2015). Therefore, protecting the relationship also means protecting oneself, as keeping the celebrity 'idolised' supports the survival of their own sense of identity and feelings of self-worth (Banister & Coker, 2014;Boon & Lomore, 2001). As such, any transgression that damages the celebrity is also likely to damage the follower.…”
Section: Consumer-related Driversmentioning
confidence: 99%
“…This was often the celebrity's high standard of achievement (Choi & Rifon, 2012). Following a transgression, seeing the celebrity return to what made them famous and successful reminded consumers why they admired the celebrity in the first place (Boon & Lomore, 2001), namely their 'achieved celebrity' status (Rojek, 2001, p. 18). The celebrity's subsequent accomplishments were a strong factor in helping repair their image and generate forgiveness by 'overriding the transgression' and focusing on the 'area of celebrification' which they were revered for:…”
Section: Celebrity-related Driversmentioning
confidence: 99%
“…Researches have shown that audience members change their appearance, attitudes, values and behaviour to resemble celebrities they admire (Boone and Lomore, 2001;Basil, 1996). Cognitive Social Theory states that viewers want to emulate attractive and successful models (Bandura, 1986).…”
Section: Involvement With the Charactermentioning
confidence: 99%